Answer:
0Step-by-step explanation:
Given,
[tex] - \frac{2}{3} [/tex]
Now, let's find the value of 9x + 6
[tex]9x + 6[/tex]
plug the value of X
[tex] = 9 \times (- \frac{2}{3} ) + 6[/tex]
Multiplying a positive and negative equals a negative
[tex]( + ) \times ( - ) = ( - )[/tex]
[tex] = - 9 \times \frac{2}{3} + 6[/tex]
Reduce the number with Greatest Common Factor 3
[tex] = - 3 \times 2 + 6[/tex]
Multiply the numbers
[tex] = - 6 + 6[/tex]
The sum of two opposites equals 0
[tex] = 0[/tex]
Hope this helps..
best regards!!
In the system of equations below, which variable would it be easiest to solve for? x + 4 y = 14. 3 x + 2 y = 12 The easiest to solve for is x in the first equation. The easiest to solve for is y in the first equation. The easiest to solve for is x in the second equation. The easiest to solve for is y in the second equation.
Answer:
The easiest to solve for is x in the first equationStep-by-step explanation:
Given the system of equation, x + 4 y = 14. and 3 x + 2 y = 12, to solve for x, we can use the elimination method of solving simultaneous equation. We need to get y first.
x + 4 y = 14............ 1 * 3
3 x + 2 y = 12 ............ 2 * 1
Lets eliminate x first. Multiply equation 1 by 3 and subtract from equation 2.
3x + 12 y = 42.
3 x + 2 y = 12
Taking the diffrence;
12-2y =42 - 12
10y = 30
y = 3
From equation 1, x = 14-4y
x = 14-4(3)
x = 14-12
x = 2
It can be seen that the easiest way to get the value of x is by using the first equation and we are able to do the substitute easily because the variable x has no coefficient in equation 1 compare to equation 2 as such it will be easier to make the substitute for x in the first equation.
Answer:
A: The easiest to solve for is x in the first equation.
Step-by-step explanation:
Please answer the following questions
Answer:
a) 8.8 square centimetres
b) 31.8 square centimetres
c) (3a + 12) square centimetres
d) Area = (2b + 2c + 4) square centimetres
Step-by-step explanation:
a) We have to split the diagram into three separate rectangles as shown below.
The area of A:
Area = 5.3 * 1 = 5.3 square centimetres
The area of B:
Area = 3.3 * 1 = 3.3 square centimetres
The area of C:
Area = 2 * 1 = 2 square centimetres
The area of the shape is the sum of the areas of the three shapes:
Area = 5.3 + 3.3 + 2 = 8.8 square centimetres
b) We have to split the diagram into two separate rectangles as shown below.
Note:(The diagram has conflicting values for 2.6 and 2.1 but I went with 2.6 as it seems more feasible in the diagram)
The area of A:
Area = 3 * 2.6 = 7.8 square centimetres
The area of B:
Area = 6 * 4 = 24 square centimetres
The area of the shape is the sum of the areas of the two shapes:
Area = 7.8 + 24 = 31.8 square centimetres
c) The shape is a rectangle and so its area is:
Area = 3 * (a + 4) = (3a + 12) square centimetres
d) The shape is a trapezium and so its area is:
Area = 0.5(A + B)H
where A = c cm
B = b + 2 cm
H = 4 cm
The area of the shape is therefore:
Area = 0.5 * (c + b + 2) * 4
Area = 2 * (b + c + 2)
Area = (2b + 2c + 4) square centimetres
Jakki got a new job that guarantees her a 6% raise every year. If she started out making $40,000, how long will it be before she doubles her current salary?
Answer:
2400months
Step-by-step explanation:
6/100*40,000
maybe
What is the reason for step 5 in this proof
Answer:
Alternate interior angles theorem
Step-by-step explanation:
DG // EF and GE is the transversal. So, alternate interior angles are congruent
Therefore, ∠HGD ≅ ∠HEF
DG // EF and DF is the transversal. So, alternate interior angles are congruent
Therefore, ∠HDG ≅ ∠HFE
Help please!!!!!!!I don’t know this! Tyy
====================================================
Explanation:
Each cube has a side length of 4. Placed together like this, the total horizontal side combines to 4+8 = 8. This is the segment HP as shown in the diagram below. I've also added point Q to form triangle HPQ. This is a right triangle so we can find the hypotenuse QH
Use the pythagorean theorem to find QH
a^2 + b^2 = c^2
(HP)^2 + (PQ)^2 = (QH)^2
8^2 + 4^2 = (QH)^2
(QH)^2 = 64 + 16
(QH)^2 = 80
QH = sqrt(80)
Now we use segment QH to find the length of segment EH. Focus on triangle HQE, which is also a right triangle (right angle at point Q). Use the pythagorean theorem again
a^2 + b^2 = c^2
(QH)^2 + (QE)^2 = (EH)^2
(EH)^2 = (QH)^2 + (QE)^2
(EH)^2 = (sqrt(80))^2 + (4)^2
(EH)^2 = 80 + 16
(EH)^2 = 96
EH = sqrt(96)
EH = sqrt(16*6)
EH = sqrt(16)*sqrt(6)
EH = 4*sqrt(6), showing the answer is choice C
-------------------------
A shortcut is to use the space diagonal formula. As the name suggests, a space diagonal is one that goes through the solid space (rather than stay entirely on a single face; which you could possibly refer to as a planar diagonal or face diagonal).
The space diagonal formula is
d = sqrt(a^2+b^2+c^2)
which is effectively the 3D version of the pythagorean theorem, or a variant of such.
We have a = HP = 8, b = PQ = 4, and c = QE = 4 which leads to...
d = sqrt(a^2+b^2+c^2)
d = sqrt(8^2+4^2+4^2)
d = sqrt(96)
d = sqrt(16*6)
d = sqrt(16)*sqrt(6)
d = 4*sqrt(6), we get the same answer as before
The space diagonal formula being "pythagorean" in nature isn't a coincidence. Repeated uses of the pythagorean theorem is exactly why this is.
You are in a panic! You forgot to buy your little brother a birthday present. You start with $60 in your wallet. You buy him several toys, t, that are $5 each. You know have $45 leftover. How many toys did you buy your little brother for his birthday? (set up the equation)
Answer: 3 toys
Step-by-step explanation:
equation will be 60 - 5 x t = 45
solving it we get
5 x t = 60 - 45 = 15
=> t = 15/5 = 3
(ugsygygsgag I’m struggling) Find the value of x in the isosceles triangle shown below
Answer:
Option B. x = 13
Step-by-step explanation:
In this question, we shall give a separate diagram which will help us to further understand the question.
Please see attached photo for further details.
To find the value of x we shall use the pythagoras theory as illustrated below:
x is the longest side Therefore,
x² = 12² + 5²
x² = 144 + 25
x² = 169
Take the square root of both side
x = √169
x = 13
Therefore, the value of x 13.
Help pleaseeee with atleast one❤️
Answer:
3) 23 cm
4)10.1
5)50
Question 4 of 10
Multiple Choice: Please select the best answer and click "submit."
What is the length of the altitude of the equilateral triangle below?
30°
6
09
a
60° 90°
3
60°
3
O A. 1
OB. 6
O C. 313
OD. 3
O E. 6.13
O F. 27
Answer:
Option C. 3√3
Step-by-step explanation:
Please see attached photo for brief explanation.
In the attached photo, we obtained the following:
Opposite = a
Adjacent = 3
Hypothenus = 6
Angle θ = 60°
We can obtain the value of 'a' as follow:
Tan θ = Opposite /Adjacent
Tan 60° = a/3
Cross multiply
a = 3 x Tan 60°
But: Tan 60° = √3
a = 3 x Tan 60°
a = 3 x √3
a = 3√3
Therefore, the length of the altitude of the equilateral triangle is 3√3.
question is in picture PLEASE HELP
Answer:
Step-by-step explanation:
Hello,
For the step 1:
We multiply the first equation by 3 and the second equation by 2, so we are using the Multiplication Property of Equality.
For the step 2:
To eliminate the x we subtract the first equation to the second one, so we are using the Subtraction Property of Equality.
For the step 3:
We divide by -16 both parts of the equation, so we are using the Division Property of Equality.
For the step 4:
We replace y in the initial first equation, we we are using the Substitution Property of Equality.
For the step 5:
We just Simplify.
For the step 6:
We add 4 to both parts of the equation, so we are using the Addition Property of Equality.
For the step 7:
We divide by 2, so we are using the Division Property of Equality.
Hope this helps.
Do not hesitate if you need further explanation.
Thank you
Which of the following represents a function
can someone help me please
Answer:
-3x
Step-by-step explanation:
-3 is the coefficient and x is the variable.
can someone please help
Answer:
C
Step-by-step explanation:
The dependent variable is always graphed on the y-axis and the independent variable is always graphed on the x-axis. Therefore, the dependent and independent variables are total price ($) and number of boxes respectively which makes the answer C.
Answer:
C. The total price depends on the number of boxes.
Step-by-step explanation:
In a graph, the x-variable is the independent variable; it is what you can change.
The y-variable is the dependent variable; its value depends on the value of the x-variable.
In this case, the y-variable is the total price of cupcakes, which depends on the x-variable, the number of boxes. C is your answer.
Hope this helps!
Solve y^2-7=2xy ; 2x^2+3=xy
with explanation and proper steps!
Answer:
what does ; resemble
Step-by-step
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Hi my lil bunny!
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
A) Let's solve for x. [tex]y^2-7=2xy[/tex]
Step 1: Flip the equation.
[tex]2xy = y^2 - 7[/tex]
Step 2: Divide both sides by 2y.
[tex]\frac{2xy}{2y} = \frac{y^2- 7}{2y}[/tex]
[tex]x = \frac{y^2- 7}{2y}[/tex]
Answer : [tex]x = \frac{y^2- 7}{2y}[/tex]
~~~~~~~~~~~~~
B) Let's solve for y. [tex]2x^2+3=xy[/tex]
Step 1: Flip the equation.
[tex]xy = 2x^2 + 3[/tex]
Step 2: Divide both sides by x.
[tex]xy = \frac{2x^2 + 3}{x}[/tex]
[tex]y = \frac{2x^2 + 3}{x}[/tex]
Answer : [tex]y = \frac{2x^2 + 3}{x}[/tex]
❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙
●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●
Hope this helped you.
Could you maybe give brainliest..?
❀*May*❀
There are 25 students in Mr. Jones’ art class. Mr. Jones is planning a project where each student needs 0.3 jar of paint. Exactly how much paint does Mr. Jones need for the art project?
Answer:
7.5 jars
Step-by-step explanation:
There are 25 students in the art class.
Mr Jones is planning that for the project, each of the 25 students will need 0.3 jar of paint.
The amount of paint Mr Jones needs for this project is therefore the product of the number of students in the class by the amount of paint each student needs.
That is:
25 * 0.3 = 7.5 jars of paint
Mr Jones needs 7.5 jars of paint for the art project.
Identify the function that best models the given data. HELP ASAP THANKS!!!
Answer:
2nd option
Step-by-step explanation:
plugging the values of x as 0,1,2,3,4,5 will help to find the exact equation
x= 0 , 199
x=1, 199* 1.25 =248.75 (approximately)
x=2, 199* (1.25)^2 = 310.9 (approximately)
x=3, 199* (1.25)^3 = 388.67 (approximately)
x=4, 199* (1.25)^4 = 485.83 (approximately)
x=5, 199* (1.25)^5 = 607.29 (approximately)
Answer: f(x) ≈ 199(1.25)^x
Step-by-step explanation:
I need answers for this please!! ;D
it is isosceles triangle as you see
so that 62 = other unknown angle
as it is a triangle interior angles sum = 180
124 + x = 180
x = 180 - 124
x = 56
Please help!! I need to get this! Brainliest For Right Anwser!
Answer:
Data set A best fit by the regression line.
Answer:
Data Set C.
Step-by-step explanation:
Well just even by common sense, the line for "data set A" is not good for the points on the graph
A walking path across a park is represented by the equation y=-3x - 3.A
new path will be built perpendicular to this path. The paths will intersect at
the point (-3,6). Identify the equation that represents the new path.
Answer:
[tex]y=\frac{1}{3} x+7[/tex]
Step-by-step explanation:
We need to find the equation of a line perpendicular to [tex]y=-3x-3[/tex], which passes through the point (-3, 6).
Recall that a line perpendicular to a line of the form: [tex]y=mx+b[/tex], must have a slope which is the opposite of the reciprocal of the slope of the original line. that is, a slope of the form;
[tex]slope=-\frac{1}{m}[/tex]
Then, in our case, since the original line has slope "-3", a perpendicular line to it should have a slope given by:
[tex]slope=-\frac{1}{-3} =\frac{1}{3}[/tex]
We now know the slope, and also a point for this new line, so we use the point-slope form of a line:
[tex]y-y_0=m_\perp\,(x-x_0)\\y-6=\frac{1}{3} (x-(-3))\\y-6=\frac{1}{3} x+\frac{3}{3} \\y-6=\frac{1}{3} x+1\\y=\frac{1}{3} x+7[/tex]
PLZ HELP QUICK!!! - Fill in the missing values in the tables. If necessary, round your answer to three decimal places.
Answer:
first blank = 10 (for table 1)
second blank = 30 (for table 2)
====================================================
Explanation:
You could use a calculator to determine the value of b, then compute b^x for that first box. But as the instructions state, we don't need to use one. Why is that? Because the tables provide enough information to fill in the blanks.
Table 1 shows x = 2.096 lead to some unknown y value. Meanwhile, table 2 has x = 10 lead to y = 2.096; note the 2.096 shows up again. The exponential and log functions are inverses of each other. They undo each other's operation. This is similar to how division undoes multiplication, and vice versa.
Going in reverse of table 2, we will conclude that 10 must go in the blank for table 1. Therefore, b^x = 10 when x = 2.096
------------
Similarly, we will have 30 in the blank for table 2. Table 1 shows x = 3.096 lead to y = 30. Table 2 is the reverse of that as it is the inverse.
Throughout either section, we didn't need to find the value of b.
The missing value in table 1 is 10 and for table 2 it is 30.
What is a logarithm?The exponent indicates the power to which a base number is raised to produce a given number called a logarithm.
In another word, a logarithm is a different way to denote any number.
In the first table first column
x = 0.369 and bˣ = 1.5 ⇒
By logarithm
logbˣ = log1.5
xlogb = log1.5
Now x = 0.369
logb = 0.1760/0.369
b = 3
Now,
f(x) at x = 2.096 ⇒ [tex]3^{2.096}[/tex] = 10
And
x at g(x) = 3.096
[tex]log_{3}[/tex]x = 3.096 ⇒ x = 30.
Hence "The missing value in table 1 is 10 and for table 2 it is 30".
For more about logarithm,
https://brainly.com/question/20785664
#SPJ2
which expression is equal to 5/ square root 11 ?
Answer:
5√11 ÷ 11 (The very last choice)
Step-by-step explanation:
I first found out what 5/√11 was and got 1.507556723 and checked all the other options and found that 5√11 ÷ 11 was the only option that had the exact same quotient as 5/√11.
PLEASE HELP ME If ƒ(x) = -x and ƒ(-3), then the result is: -3. 0. 3. None of these choices are correct.
Answer:
The answer is 3.
Step-by-step explanation:
This is because f(-3) = -(-3) = 3.
Please help me... tysm if you do
Answer:
The answer is B.
Step-by-step explanation:
Since x < 1 the circle at the point is open and the arrow points infinitely in the negative direction (which happens to be answer A here)
x is also greater than or equal to -1 so a closed circle at the point -1 will complete this graph.
When deriving the quadratic formula by completing the square, what expression can be added to both sides of the equation to create a perfect square trinomial?
Answer:
According to steps 2 and 4. The second-order polynomial must be added by [tex]-c[/tex] and [tex]b^{2}[/tex] to create a perfect square trinomial.
Step-by-step explanation:
Let consider a second-order polynomial of the form [tex]a\cdot x^{2} + b\cdot x + c = 0[/tex], [tex]\forall \,x \in\mathbb{R}[/tex]. The procedure is presented below:
1) [tex]a\cdot x^{2} + b\cdot x + c = 0[/tex] (Given)
2) [tex]a\cdot x^{2} + b \cdot x = -c[/tex] (Compatibility with addition/Existence of additive inverse/Modulative property)
3) [tex]4\cdot a^{2}\cdot x^{2} + 4\cdot a \cdot b \cdot x = -4\cdot a \cdot c[/tex] (Compatibility with multiplication)
4) [tex]4\cdot a^{2}\cdot x^{2} + 4\cdot a \cdot b \cdot x + b^{2} = b^{2}-4\cdot a \cdot c[/tex] (Compatibility with addition/Existence of additive inverse/Modulative property)
5) [tex](2\cdot a \cdot x + b)^{2} = b^{2}-4\cdot a \cdot c[/tex] (Perfect square trinomial)
According to steps 2 and 4. The second-order polynomial must be added by [tex]-c[/tex] and [tex]b^{2}[/tex] to create a perfect square trinomial.
Answer: D
Step-by-step explanation:
EDGE 2023
A student who is 5ft tall and cast a shadow 8ft long.at the Same time a flag shadow is 24ft long.how long is the flag?
Answer:
The long of the flag is:
15 ft
Step-by-step explanation:
On a three rule:
5 ft is to 8 ft
24 ft is to A ft
A = 24*5/8
A = 15 ft
related task: https://brainly.com/question/17139181
An annual salary is $45000. His tax free allowances total $13000. He has to pay a tax of 20% on his taxable income.
The tax payable is?
Answer:
6400
Step-by-step explanation:
Taxable amount=45000-13000=32000
tax=32000*20/100
=6400
At a boating and sport store the cost of renting a personal watercraft is $64.20 per half hour, which includes a 7% sales tax. Determine the cost of a half hour rental before tax
Answer: $60
Step-by-step explanation:
Given the following :
Total cost of renting a personal water craft = $64.20
Sales tax charged = 7%
Let the pretax cost = y
Therefore,
total cost = pretax cost + tax
$64.20 = y + 7% of y
$64.20 = y + 0.07y
$64.20 = 1.07y
y = $64.20 / 1.07
y = $60
Therefore, the rental cost of a personal watercraft for half an hour before tax is $60
A jar of jam contains 55% fruit.How much fruit would I need for ten 454g jars of jam?
Answer: 10x454x0.55=2,497 grams of fruit
factorise
1)
8a(3x–2y)²–12x +8y
Answer:
Step-by-step explanation:
Hello,
[tex]8a(3x-2y)^2-12x +8y\\\\ = 8a(3x-2y)^2-4(3x-2y)\\\\ = (3x-2y)(8a(3x-2y)-4)\\\\=(3x-2)(24ax-16ay-4)[/tex]
Hope this helps.
Do not hesitate if you need further explanation.
Thank you
Please answer this question now
Answer:
[tex]\boxed{u = 13.7}[/tex]
Step-by-step explanation:
Using cosine rule
[tex]c^2 = a^2+b^2-2ab\ CosC[/tex]
Here c = u, a = 9 , b = 21 and C = 28
[tex]u^2 = 9^2+21^2-2(9)(21)\ Cos 28\\u^2 = 81+441-(378)(0.88)\\u^2 = 522 - 333.75\\u^2 = 188.24[/tex]
Taking sqrt on both sides
u = 13.7
Answer:
u ≈ 13.7
Step-by-step explanation:
Using the Cosine rule in Δ STU, that is
u² = s² + t² - 2stcosU
Here s = 21, t = 9 and U = 28°, thus
u² = 21² + 9² - (2 × 21 × 9 × cos28°)
= 441 + 81 - 378 cos28°
= 522 - 378 cos28° ( take the square root of both sides )
u = [tex]\sqrt{522-378cos28}[/tex]
≈ 13.7 ( to the nearest tenth )